Choreographies of Shared Sacred Sites: Religion, Politics, and Conflict Resolution - Barkan, Elazar; Barkey, Karen (Religion, Culture, and Public Life, 2014)
Anna Bigelow, North Carolina State University:Coming from a range of disciplines, the essays in Choreographies of Shared Sacred Sites are compelling for specialists in interreligious relations, conflict resolution and peace studies, and religious ethnography. They are also engaging and accessible to a general audience concerned with the related issues of pluralism, coexistence, conflict, and tolerance. Understanding the complexity of shared sites is essential to grasping the ways multiple religions jointly inhabit this plural world. A valuable and timely volume in a field critical to the present moment in history. Charles Stewart, University College London:Sacred sites are ideally intimate possessions, inviolable and holy. Sharing them with other communities is like splitting an atom. This timely collection allows readers to examine the choreographies of theological politics and political theologies scripted to contain potential eruptions of violence, and these highly readable case studies will fuel discussions of the post-Ottoman era for many years to come. Maria Couroucli, Centre National de la Recherche Scientifique, Laboratoire d'Ethnologie et Sociologie Comparative:A most welcome addition to the growing literature on sharing sacred spaces in the eastern Mediterranean, with special reference to practices of coexistence between Christians and Muslims in the Ottoman and post-Ottoman traditions. This collection goes beyond the dilemma of 'peaceful coexistence and syncretic practices' versus 'antagonism and conflict.' Contributions focus on interreligious relations during the transition from empire to nation and on present-day